Prevalence of Helminthiasis in Slaughterhouse Medan - Mudhita Zikkrullah Ritonga; Andhika Putra (Indonesian Journal of Agricultural Research, 2018)
Factors affecting the success of the livestock business are feed and disease control. The aim of this study to determine the prevalence of helminthiasis in Slaughterhouse Mabar Medan City. The type of this research is survey research with portrait and analysis of a condition of cattle condition that will be slaughterhoused in Slaughterhouse Mabar Medan City in a certain time. The design of this study is observation or direct observation to the field to see the existing events without intervening from the researcher. The sampling technique is determined by purposive sampling (purposive determination of respondents). Methods of data retrieval is done by observation method that is data retrieval method done by systematically record the result of observation to the events investigated during the research. The result of research in Slaughterhouse Mabar Medan city shows that the prevalence of helminthiasis is 0%. From this result shows the cows that were slaughtered by Slaughterhouse Mabar Medan City is free from the parasitic worm disease.